Optimising Outcomes in Rehabilitation of Lower Limb Amputation - Roffman, Caroline Eileen (Curtin University, 2017)
Limited research exists on outcomes following lower limb amputation. This is the first study to develop and validate Clinical Prediction Rules for prosthetic non-use at 4, 8 and 12 months after rehabilitation discharge. Performance thresholds that identify increased risk of prosthetic non-use have been generated for locomotor tests. Long term outcomes and comorbidities have been described for people with lower limb amputation. This thesis has contributed to evidence based health reform to models of care.